A formative approach to the evaluation of Transformative Innovation Policies. Issue 4 (5th August 2021) - Molas-Gallart, Jordi; Boni, Alejandra; Giachi, Sandro; Schot, Johan
Abstract: Transformative Innovation Policies (TIPs) assert that addressing the key challenges currently facing our societies requires profound changes in current socio-technical systems. To leverage such 'socio-technical transitions' calls for a different, broad mix of research and innovation policies, with particular attention being paid to policy experiments. As TIPs diffuse and gain legitimacy they pose a substantial evaluation challenge: how can we evaluate these policy experiments with a narrow geographical and temporal scope, when the final objective is ambitiously systemic? How can we know whether a specific set of policy experiments is contributing to systemic transformation? Drawing on TIPs principles as developed by and applied in the activities of the Transformative Innovation Policy Consortium and on the concept of transformative outcomes, this article develops an approach to the evaluation of TIPs that is operational and adaptable to different contexts.